Towards an Adaptive Bureaucracy: An Analysis of the Implementation of Flexible Working Arrangements (FWA) in the Surabaya City Government in 2025 - Helena Fatma Saragih Sitio; Arief Rachmat Fauzi; Haji Munawwarah; Eko Purwanto; Nanik Wulandari Sudiastuti (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This study analyzes the implementation of FWA in Surabaya City, using a qualitative approach. The results indicate that FWA has been implemented systematically, adaptively, and digitally, supported by local regulations, structured work mechanisms, and the utilization of the Kantorku application for attendance tracking, reporting, and performance monitoring of the ASN. The implementation of this policy is considered quite effective in maintaining the quality of public services, increasing operational budget efficiency, and driving a shift in the ASN work culture to a results oriented approach. However, several obstacles were identified, such as supervision limitations for roles requiring physical presence, variations in leadership managerial capacity to manage flexible work, the risk of reduced discipline and work coordination, and a high dependence on digital infrastructure and the digital literacy of the ASN. The study recommends strengthening leadership managerial capacity through digital leadership training and performance based supervision, developing continuous data driven monitoring and evaluation systems, enhancing ASN digital literacy, and implementing a hybrid working model tailored to job characteristics and organizational needs. Furthermore, this research emphasizes that FWA has the potential to serve as a strategic instrument to support a more adaptive, efficient, and public service oriented bureaucratic reform in the digital transformation era. Nevertheless, this study has limitations as it focuses on a single local government with a limited informants; thus, the findings cannot be fully generalized to the broader context of government bureaucracy in Indonesia.